2003
DOI: 10.1109/twc.2002.806356
|View full text |Cite
|
Sign up to set email alerts
|

On CDMA with space--time codes over multipath fading channels

Abstract: We explore in this paper code division multiple access systems with multiple transmitter and receiver antennae combined with algebraic constellations over a quasi-static multipath fading channel. We first propose a technique to obtain transmit diversity for a single user over quasi-static fading channels by combining algebraic constellations with full spatial diversity and spreading sequences with good cross-correlation properties. The proposed scheme is then generalized to a multiuser system using the same al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…(31)]) does not offer full diversity. Damen et al proposed a class of high-rate full-transmit diversity-based space-time CDMA systems in [23]. However, they actually use space codes instead of space-time codes.…”
Section: B Fdfr Ldcmentioning
confidence: 99%
See 2 more Smart Citations
“…(31)]) does not offer full diversity. Damen et al proposed a class of high-rate full-transmit diversity-based space-time CDMA systems in [23]. However, they actually use space codes instead of space-time codes.…”
Section: B Fdfr Ldcmentioning
confidence: 99%
“…However, they actually use space codes instead of space-time codes. Note that in [23], N t source data symbols are transformed using a signal space diversity rotation to obtain N t coded symbols, and each of the coded symbols is spread through a signature sequence. Although these spread symbols are over time, the signatures are not spread over multiple data symbols.…”
Section: B Fdfr Ldcmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the number of receive antennas is greater than two, it has been shown that the Alamouti scheme loses some multiplexing gain [7], and thus, is not optimal. Applying the diagonal ST codes to DS/CDMA was proposed in [8]. Again, this system has to be synchronous and use orthogonal spreading codes to separate different transmit antennas.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the diversity-multiplexing tradeoff is concerned [7], we adopt the threaded algebraic space-time (TAST) code recently proposed in [8], which can achieve the full transmission rate as well as maintain the full diversity gain. In asynchronous DS/CDMA, chip-level oversampling is usually followed by an MMSE detector to suppress the MAI [3].…”
Section: Introductionmentioning
confidence: 99%